Autism kids learning tools: Magic board / Zarina Begum Ebrahim … [et al.] - Ebrahim, Zarina Begum; W Muda, W. Atiqah; Norman, Halimah; Shaiful Azhar, Nurfarisha Idayu; Mat Kasim, Nurul Jannah; Othman, Noraini; Mokhtar, Noorzalyla; Mustakim, Nurul Ain; Sauid, Muna Kameelah (Division of Research and Industry Linkages, 2017)
The product is relating to the innovation of Autisms kid learning tools: Magic Board was design especially for autism kids. The Magic Board was produced in a variety of games that can attract the autism kids in their learning disabilities as well as to improve their thinking skills. The purpose o f Magic Board in this autism learning tools is to boost up their interest towards variety of learning skills and provide an opportunity for autism children to show their hidden talents, The present innovation also relates to the problems o f autism children in learning process which are difficulties to memorize such as alphabet, colour and shape and have trouble in focusing and concentrating in learning attention. Therefore, the magic board was created to develop uniqueness learning tools for children which is very convenient to bring anywhere and multifunction board which consist o f three variety o f games in a board. Moreover, the kids also will be easy to memorize the colour, alphabet and shape through the attractive colours that we have been used in the Magic Board. The kids also will explore and can show their talent and creativity by playing our Magic Board. The present innovation was targeted specifically for autism children to provide good learning tools through the learning process.